2020
DOI: 10.1002/qj.3943
|View full text |Cite
|
Sign up to set email alerts
|

Sub‐km scale numerical weather prediction model simulations of radiation fog

Abstract: The numerical weather prediction (NWP) of fog remains a challenge, with accurate forecasts relying on the representation of many interacting physical processes. The recent Local And Non‐local Fog EXperiment (LANFEX) has generated a detailed observational dataset, creating a unique opportunity to assess the NWP of fog events. We evaluate the performance of operational and research configurations of the Met Office Unified Model (MetUM) with three horizontal grid lengths, 1.5 km and 333 and 100 m, in simulating f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 70 publications
0
31
0
Order By: Relevance
“…The IGP region is shrouded in a layer of thick fog, and apart from the regional meteorology, an adequate amount of moisture provided to the atmosphere comes from the wet soil, which is a result of irrigation (Izhar et al 2020 ; Ghude et al 2017 ). In his research, Smith et al ( 2021 ) found that the fog was highly sensitive to the thermal conductivity of soil, causing the onset time of fog to shift by 5 h. Adhikari and Wang ( 2020 ) made the first attempt to study the influence of soil moisture on fog. The study was conducted at two sites of Namib Desert, one is a gravel plain, and the other is a sand dune.…”
Section: Factors Influencing Fog Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…The IGP region is shrouded in a layer of thick fog, and apart from the regional meteorology, an adequate amount of moisture provided to the atmosphere comes from the wet soil, which is a result of irrigation (Izhar et al 2020 ; Ghude et al 2017 ). In his research, Smith et al ( 2021 ) found that the fog was highly sensitive to the thermal conductivity of soil, causing the onset time of fog to shift by 5 h. Adhikari and Wang ( 2020 ) made the first attempt to study the influence of soil moisture on fog. The study was conducted at two sites of Namib Desert, one is a gravel plain, and the other is a sand dune.…”
Section: Factors Influencing Fog Formationmentioning
confidence: 99%
“…The influence of soil properties on fog formation has not been analytically studied, neither in field studies nor as an important parameterization factor in prediction models. Smith et al ( 2021 ) have studied the impact of both grass and bare soil on fog; nevertheless, they have also suggested that future research is needed on to what extent grass can act as an insulator between soil and atmosphere.…”
Section: Factors Influencing Fog Formationmentioning
confidence: 99%
“…The model set up is 300 × 300 horizontal grid-points, centred on the Auckland Harbour Bridge with a terrain-following 140-level vertical coordinate system over the lowest 40 km of the atmosphere. This increased resolution has shown significant improvements of near surface temperatures [30,31]. The Auckland Model is one-way nested inside NIWA's 4-km resolution NZLAM (New Zealand Limited Area Model), which is data-assimilating and uses the Global Atmosphere 6 science configuration [32] with an intermediate nest at 1.5 km resolution to ease the transition from 4-km to 333-m resolution.…”
Section: Methods and Datamentioning
confidence: 99%
“…is greatest closest to the surface, where they increase the amount of (Q c ) removed from the lowest model levels". Boutle et al (2016Boutle et al ( , 2018 and Smith et al (2021) have adjusted the MetUM taper parameters and obtained improved matches with visibility observations of fog, including the LANFLEX (Price et al, 2018) study. It seems to work as a "tuning parameter", but the taper curve approach could be considered somewhat unphysical.…”
Section: Operational Numerical Weather Prediction (Nwp) Modelsmentioning
confidence: 98%
“…13c from Bergot et al (2005), generally show Q c maxima at the surface. COBEL has also been coupled with WRF (Stolaki et al, 2012) and used to simulate advectionradiation fog conditions at Thessaloniki Airport. Ducongé et al (2020) report on recent radiation fog modelling studies with Meso-NH downscaled from the Métèo-France operational model of AROME.…”
Section: Model Studiesmentioning
confidence: 99%